Pengaruh Brand Awareness, Sertifikasi Halal, Dan Social Media Influencer Terhadap Keputusan Pembelian Konsumen Muslim Reddog Cabang Delipark Mall Medan - Oka Sutansyah Ariara Siregar; Ahmad Kholil (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This research was conducted to determine the influence of Brand awareness, halal certification, and social media influencers on the purchasing decisions of Muslim consumers at the Reddog Delipark Mall Medan branch. The sample used in this study consisted of 100 respondents, namely Muslim consumers of Reddog Delipark Mall Medan, and questionnaires were used as primary data. The questionnaire data collection technique is evaluated using a Likert scale, validity test, and reliability test. The results of the partial test showed that the Brand awareness variable had a positive and significant partial effect with a significance level of 0.000, the halal certification variable had a positive and significant partial effect with a significance level of 0.027, and the social media influencer variable had a positive and significant partial effect with a significance level of 0.000 on Muslim consumer purchasing decisions for Reddog. Simultaneously, the Brand awareness, halal certification, and social media influencer variables had a positive and significant effect on Muslim consumer purchasing decisions for Reddog Delipark Mall Medan branch with a significance level of 0.000.